The impact of the approaches of interpretive schools on the differences among interpreters - the rulings of Surat At-Talaq as a model - Aws Nazim Saleh, (Islamic Sciences Journal, 2025)
This research explores the schools of Qur’anic exegesis (Tafsir), their methodologies, and their impact on differences among exegetes (mufassirūn). The importance of the topic lies in the elevated status of Tafsir, being directly connected to the Book of Allah, the Exalted, and Its role in explaining divine guidance and rulings. Adopting a descriptive, analytical, and inductive methodology, the study begins by defining Tafsir linguistically and terminologically, and tracing its historical development. It then examines the emergence of various schools of exegesis, their distinct methods, and how these have shaped interpretive differences—especially regarding rulings on divorce and ‘iddah (waiting period). The research finds that Tafsir bi’l-Ma’thūr (transmitted exegesis) is the earliest school, characterised by interpreting the Qur’an through the Qur’an, the Sunnah, and the sayings of the Companions and Successors. In contrast, scholars are divided over Tafsir bi’l-Ra’y (opinion-based exegesis): some reject it, viewing it as speaking about Allah without knowledge, while others permit it under strict scholarly conditions and with supporting evidence.